Kajian Keragaman Plankton dan Ikan di Perairan Teluk Tanah Merah Distrik Depapre, Kabupaten Jayapura, Papua - Puguh Sujarta; Henderite L. Ohee; Erlani Rahareng (Jurnal Biologi Papua, 2011)
Papua has a potensial marine resources both in ecology aspect as well as in economic. To keep the richness of marine resources, conservation is needed. Tiyaitiki is a traditional conservation based on indigenous knowledge of local people of Teluk Tanah Merah Depapre Jayapura. They used their custom to conserve both the water areas and the natural resources as well. The aims of the study were to observe the diversity of plankton and fishes in Teluk Tanah Merah, and to know the quality of water based on that diversity. Research was conducted from July to August 2007.  Line transect method was used in this study. Datawere collected from three station,  at morning, noon, dawn and night separately.The result of the study were 38 genera of plankton, 21 genera of fithoplankton and 17 genera of zooplankton. Moreover, the result of fish diversity survey was 62 species. Those indicated that the water areas in Teluk Tanah Merah Depapre was in a good qualityfor fish life. Key words:  plankton, fish, Tiyaitiki, Jayapura, Papua